2012
DOI: 10.1155/2012/169545
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Disease of the Femur with an Extraosseous Extent due to a Former Biopsy Complicated by a Pathological Fracture

Abstract: Hydatid disease of the bone represents about 1–2.5% of all human hydatid disease. Spine is the most affected part of the skeleton with 50% incidence of all bone hydatidosis. Extraspinal bone hydatidosis is much rare. Diagnosis is difficult in the bone hydatid disease. Bone tumors, tumor-like lesions, and specific and nonspecific infections should be considered in the differential diagnosis. Radiological, laboratory, and clinical findings combined with strong element of suspicion are the key for diagnosis. Bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The patient then underwent en bloc excision of the hydatid cyst with curettage and the gap was filled with bone cement. Ciftdemir et al reported a case of bone hydatidosis of the femoral shaft which was managed with surgical debridement and excision of the cyst [ 10 ]. However, 10 days after discharge, the patient presented with a pathological fracture of the shaft of femur which was treated with a custom made intra-medullary inter-locking nail.…”
Section: Discussionmentioning
confidence: 99%
“…The patient then underwent en bloc excision of the hydatid cyst with curettage and the gap was filled with bone cement. Ciftdemir et al reported a case of bone hydatidosis of the femoral shaft which was managed with surgical debridement and excision of the cyst [ 10 ]. However, 10 days after discharge, the patient presented with a pathological fracture of the shaft of femur which was treated with a custom made intra-medullary inter-locking nail.…”
Section: Discussionmentioning
confidence: 99%
“…They usually present with atypical imaging features and laboratory tests, hence posing a diagnostic problem and thus delaying treatment in early stages [ 6 ]. Differential diagnosis may include tumors and tumor-like lesions of the bone, tuberculosis, and fungal infections [ 7 ]. Echinococcal bone lesions may be unifocal or appear in multiple locations [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection by the parasitic Echinococcus tapeworm genus causes hydatid disease 1-5 . Hepatic disease and pulmonary disease are the first and second most common infection sites, respectively 1,2,6-14 . Further dissemination is rare, and osseous involvement is particularly uncommon 1-5,8,10,13,15 .…”
mentioning
confidence: 99%
“…Further dissemination is rare, and osseous involvement is particularly uncommon 1-5,8,10,13,15 . Spine and pelvis are the first and second most frequent osseous disease sites, respectively 1,4,5,8-12,15,16 . Femoral involvement is less common 4,5,8,9,11,12,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation